2018
DOI: 10.1177/1533033818758905
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a Functions as a Tumor Suppressor and Increases Cisplatin Sensitivity by Targeting NRAS in Lung Cancer

Abstract: MicroRNAs have been reported to play an important role in diverse biological processes and progression of various cancers. MicroRNA-29a has been observed to be downregulated in human lung cancer tissues, but the function of microRNA-29a in lung cancer has not been well investigated. In this study, we demonstrated that the expression levels of microRNA-29a were significantly downregulated in 38 pairs of lung cancer tissues when compared to adjacent normal tissues. Overexpression of microRNA-29a inhibited the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Our data showed that circulating plasma miRNA-17 and miRNA-222 expression levels were significantly higher in patients with NSCLC than those in healthy controls (P=0.000). In accordance with our findings, previous studies have shown that aberrant miRNA expression in NSCLC patients' blood and healthy individuals is powerfully associated with cancer development and progress (Xu et al, 2015;Zaporozhchenko et al, 2018;Yang et al, 2018;Liu et al, 2018;Liu and Wang, 2017). Contrary to such speculations, Li et al, (2013) have revealed that the expression of miR-17-5p is reduced in triple-negative breast cancer tissues and that it can suppress tumor progression through inhibition of ETV1 oncogene in triple-negative breast cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that circulating plasma miRNA-17 and miRNA-222 expression levels were significantly higher in patients with NSCLC than those in healthy controls (P=0.000). In accordance with our findings, previous studies have shown that aberrant miRNA expression in NSCLC patients' blood and healthy individuals is powerfully associated with cancer development and progress (Xu et al, 2015;Zaporozhchenko et al, 2018;Yang et al, 2018;Liu et al, 2018;Liu and Wang, 2017). Contrary to such speculations, Li et al, (2013) have revealed that the expression of miR-17-5p is reduced in triple-negative breast cancer tissues and that it can suppress tumor progression through inhibition of ETV1 oncogene in triple-negative breast cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…in addition, mir-29a was predicted to interact with circ_087212. mir-29a was identified to regulate malignant cell features and drug resistance in several cancer types, including hepatocellular cancer and lung cancer by targeting Sirtuin 1 and nraS (15,28). Based on the present results, identifying novel approaches that may target and affect the stability of the interaction between circrna and mirnas may be important for inhibiting cancer metastasis, invasiveness and recurrence.…”
Section: Discussionmentioning
confidence: 62%
“…MicroRNAs (miRNAs) were a quantity of short non-coding RNAs that could inhibit the function of target genes through degrading the mRNA or suppressing its translation in post-transcriptional regulation 4,5. MiR-29a has been reported to be a tumor suppressors and was participated in the proliferation of glioma and lung cancer 6,7. Xiong et al8 revealed that miR-29a inhibited the growth and metastasis through targeting BMI1 in melanoma.…”
Section: Introductionmentioning
confidence: 99%